"I have turned into a foreman here at home": Families and work–life balance in times of COVID‐19 in a gender equality paradise. Issue 1 (9th October 2020) - Hjálmsdóttir, Andrea; Bjarnadóttir, Valgerður S.
Abstract: This article explores the gendered realities of work–life balance in Iceland during the COVID‐19 pandemic, in particular how these societal changes reflect and affect the gendered division of unpaid labor, such as childcare and household chores. The study draws on open‐ended real‐time diary entries, collected for 2 weeks during the peak of the pandemic in Iceland. The entries represent the voices of 37 mothers in heteronormative relationships. The findings imply that, during the pandemic, the mothers took on greater mental work than before. They also described intense emotional labor, as they tried to keep everyone calm and safe. The division of tasks at home lay on their shoulders, causing them stress and frustration. The findings suggest that, even in a country that has been at the top of the Gender Gap Index for several years, an unprecedented situation like COVID‐19 can reveal and exaggerate strong gender norms and expectations toward mothers.